Flexible composite material capable of being directly engraved by laser as well as preparation method and application of flexible composite material
Through direct laser engraving technology of phenolic resin and PDMS, the problem of high cost and complex process of flexible wearable sensor preparation methods is solved, the sensitivity and stability of the material is improved, and high-efficiency and low-cost large-scale production and high-precision laser are achieved. Engraving, suitable for complex environmental applications.
Patent Information
- Application Number
- CN202411363684.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-28
- Publication Date
- 2025-01-03
AI Technical Summary
The existing flexible wearable sensor preparation methods are costly, complex in process, insufficient material sensitivity and stability, making it difficult to achieve efficient and low-cost large-scale production, and are easily affected by mechanical stress during long-term use, resulting in decreased sensitivity.
Flexible composite materials are prepared by direct laser engraving technology using phenolic resin and PDMS. A uniform film is formed by adjusting the material proportion and spin coating process, and combined with heating and curing treatment, the process is simplified and the flexibility and stretchability of the material are improved.
Significantly reduces production costs, simplifies the preparation process, improves the sensitivity and stability of the material, enhances the fit and adhesion with human skin, is suitable for large-scale production, and supports high-precision laser engraving, extending the sensor Service life.
Smart Images

Figure CN119242046A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flexible composite material capable of being directly laser engraved and a preparation method and application thereof, belonging to the field of functional composite materials. Background Art
[0002] With the development of wearable devices, flexible wearable sensors have been widely used in medical health monitoring, sports tracking, environmental detection and other fields. Traditional flexible wearable materials are mainly composed of conductive polymers, conductive fibers or film materials. These materials have certain flexibility and stretchability and can adapt to the dynamic activities of the human body. Existing methods for preparing flexible wearable sensors mainly include solution processing, spraying, printing, etc., but these traditional materials and preparation methods have certain limitations and challenges in practical applications.
[0003] 1. High cost: Existing solution processing and spraying methods usually use high-cost raw materials and complex process steps. The preparation process of materials such as carbon nanotubes, graphene and conductive polymers is complicated and requires the use of expensive chemical reagents. Although technologies such as spraying and printing can be mass-produced, the equipment investment is high, resulting in excessively high overall production costs.
[0004] 2. Complex preparation process: The existing preparation process has many steps and complex operations, making it difficult to achieve efficient and low-cost large-scale production. For example, the solution treatment method requires multiple coatings and drying, and the spraying method and printing method require precise control of equipment parameters and environmental conditions.
[0005] 3. Sensitivity and stability: The sensitivity and stability of flexible wearable sensors are important factors affecting their performance. Sensors prepared by solution processing often have problems with uneven conductive networks, resulting in low sensor sensitivity and slow response speed. Sensors prepared by spraying and printing methods are susceptible to mechanical stress in the long-term use of the conductive layer, resulting in decreased sensitivity and signal drift.
[0006] 4. Insufficient flexibility and stretchability: While flexible sensors prepared using existing technologies meet basic flexibility requirements, their stretchability and mechanical properties are often insufficient, making it difficult for them to withstand large deformation and stretching, limiting their application in complex environments.
[0007] Therefore, there is an unmet need in the art for flexible, wearable composite materials that can be directly laser engraved. Summary of the invention
[0008] In order to solve the above problems, the present invention provides a flexible wearable composite material that can be directly laser engraved and a preparation method thereof, which not only reduces the production cost and simplifies the preparation process, but also improves the sensitivity and stability of the material as well as the fit and adhesion of the material to human skin, and gives the material better flexibility and stretchability, thereby significantly improving the performance and application prospects of flexible wearable sensors.
[0009] Specifically, in one aspect, the present invention provides a flexible composite material that can be directly laser engraved, characterized in that the composite material is obtained by mixing phenolic resin, PDMS and PDMS curing agent to form a film.
[0010] Furthermore, the mass ratio of the phenolic resin to PDMS is 0.25-0.75:1, preferably 0.5:1.
[0011] Furthermore, the mass ratio of the PDMS curing agent to PDMS is 1:8-12, preferably 1:10.
[0012] As used herein, the specific selection of phenolic resin is not limited, and it can be any suitable phenolic resin. For example only, the phenolic resin can be BR2123, which has thermosetting properties, white to light yellow powder appearance, free phenol content ≤4.5%, softening point of 98-115°C, moisture content less than or equal to 1.5%, and hexamethylenetetramine content of 7%-9%.
[0013] As used herein, PDMS refers to polydimethylsiloxane.
[0014] As used herein, a PDMS curing agent can be any agent that can cause PDMS to undergo cross-linking and curing under certain conditions (e.g., heating). Such PDMS curing agents are well known in the art. By way of example only, the PDMS curing agent includes, but is not limited to, at least one of methyltriethoxysilane, methyltripropoxysilane, or γ-aminopropyltriethoxysilane.
[0015] In one example, the PDMS is Dow Corning DC184 PDMS, which includes a PDMS base component and a curing agent. When used, the base component and the curing agent are completely mixed at a weight ratio of 10:1.
[0016] In other aspects, the present invention also provides a method for preparing a flexible composite material that can be directly laser engraved as described herein, the method comprising uniformly mixing phenolic resin, PDMS and PDMS curing agent and coating the mixture on a substrate surface, and curing the mixture into a film to obtain the flexible composite material that can be directly laser engraved.
[0017] Furthermore, the coating is performed by spin coating.
[0018] Furthermore, the spin coating conditions are: a rotation speed of 200-1000 rpm (preferably 500 rpm) and a time of 60 seconds.
[0019] Furthermore, the substrate may be any substrate suitable for film making, for example, a glass sheet.
[0020] Furthermore, a sacrificial layer is coated on the surface of the substrate to facilitate separation of the flexible composite material that can be directly laser engraved from the substrate after film formation. For example, the sacrificial layer can be a mixed solution of polyacrylic acid solution and isopropanol. Furthermore, the mass of the polyacrylic acid solution in the mixed solution is 5% of the mass of isopropanol. The polyacrylic acid solution can be an aqueous solution of polyacrylic acid, and the concentration of polyacrylic acid can be 30-40wt.%.
[0021] Furthermore, the curing may include heat curing or other appropriate curing methods. For example, the heat curing may be performed at a temperature of 60-90° C. for 1-3 hours.
[0022] Furthermore, the method further comprises separating the film from the substrate and drying the film after curing to form the film.
[0023] In other aspects, the present invention also provides use of the directly laser-engravable flexible composite material as described herein for laser engraving.
[0024] Furthermore, the laser power of the laser engraving may be 9.5-11.5 watts, and the engraving speed may be 1080-1800 mm / s.
[0025] In other aspects, the present invention also provides a use of the flexible composite material that can be directly laser-engraved as described herein for preparing a flexible sensor.
[0026] Beneficial effects of the present invention
[0027] In one embodiment, the present invention uses thermosetting phenolic resin powder and PDMS to mix in a suitable ratio, and forms a uniform film structure through a precisely controlled spin coating process. By adjusting the rotation speed of the spin coating, the thickness of the film can be flexibly controlled, so that the material can achieve an optimal balance between flexibility, stretchability and laser engraving adaptability. The mixed material is subjected to a heat curing treatment at a specific temperature, so that the phenolic resin can be fully cross-linked to form a composite film with excellent thermal stability and mechanical strength. At the same time, PDMS provides excellent flexibility and elasticity, so that the film can not only adapt to various movements of the human body, but also maintain good mechanical properties and stability. Finally, through the stripping process, this optimized flexible film is obtained, which can be directly subjected to high-precision laser engraving and is suitable for the design of a variety of complex patterns and structures.
[0028] The material selection and process of the present invention are relatively simple, the cost of raw materials is low, and the preparation process does not require complex equipment and operations, which significantly reduces the overall preparation cost, is suitable for large-scale production, and has high economic benefits. The present invention prepares a thin film material with good flexibility and stretchability by optimizing the ratio of phenolic resin powder to PDMS. The material can adapt to the curved shape of human skin, has a high degree of fit, and is suitable for use in flexible wearable devices. Compared with the prior art, the material of the present invention can still maintain stable performance under high load and repeated stretching conditions, and is particularly suitable for flexible sensors that require long-term reliability. The composite material of the present invention supports programmable and erasable high-precision direct laser engraving, eliminates complex post-processing steps, and achieves high-precision and high-efficiency microstructure processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 and 2 are stress-strain curves of the composite materials obtained in Examples 1, 2 and 3 of the present invention.
[0030] Figure 2 The Young's modulus bar graph of the composite materials obtained in Examples 1, 2 and 3 of the present invention.
[0031] Figure 3 1 and 2 are stress-strain curves of the composite materials obtained in Comparative Examples 1, 2 and 3 of the present invention.
[0032] Figure 4 1 and 2 are stress-strain curves of the composite materials obtained in Comparative Examples 4, 5 and 6 of the present invention.
[0033] Figure 5 The sensitivity curves of the composite materials obtained in Examples 1, 6 and 7 of the present invention treated with different laser powers in the range of 0-100 KPa.
[0034] Figure 6 The sensitivity curves of the composite materials obtained in Examples 1, 8 and 9 of the present invention processed at different laser speeds within the range of 0-100 KPa.
[0035] Figure 7 This is a resistance-strain curve diagram of the composite material obtained in Example 1 of the present invention after laser engraving.
[0036] Figure 8 This is a resistance-strain curve diagram of the composite material obtained in Example 6 of the present invention after laser engraving.
[0037] Fig. 9 This is a resistance-strain curve diagram of the composite material obtained in Example 7 of the present invention after laser engraving.
[0038] Fig.10 This is the current change rate at a pressure of 65 Pa after laser engraving of the composite material obtained in Example 1 of the present invention.
[0039] Fig.11 This is the current change rate at a pressure of 353 Pa after laser engraving of the composite material obtained in Example 1 of the present invention.
[0040] Fig.12 This is the current change rate at a pressure of 2060 Pa after the composite material obtained in Example 1 of the present invention is laser engraved.
[0041] Fig.13 This is a SEM image of the composite material obtained in Example 1 of the present invention taken after laser engraving.
[0042] Fig.14 This is a SEM image of the composite material obtained in Example 1 of the present invention after being laser engraved and stretched to a strain of 40%. DETAILED DESCRIPTION
[0043] The present invention provides a flexible wearable composite material that can be directly laser engraved. The specific preparation steps of the composite material are as follows: step 1: a certain proportion of phenolic resin powder and PDMS are completely mixed by a manual stirring method, and the formed mixture is coated on a glass sheet that forms a sacrificial layer; step 2: spin coating is performed to form a uniform film thickness, and then placed on a hot stage for heating and curing to form a flexible composite material that can be directly laser engraved.
[0044] The present invention is further described below in conjunction with specific examples, but the examples do not limit the present invention in any form. In the examples, the brands of PDMS and PDMS curing agent are Dow Corning DC184, the phenolic resin is BR2123, the EcoFlex brand is American Smooth-On Ecoflex0030, the water-based polyurethane emulsion brand is Anda Huatai AH-1618, the laser engraving machine is purchased from Shanghai Diaotu T1 Pro, and the polyacrylic acid solution is an aqueous solution of polyacrylic acid with a concentration of 35wt.%, and an average molecular weight Mw~100000. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0045] Example 1
[0046] 1g PDMS, 0.1g PDMS curing agent, and 0.5g phenolic resin powder were weighed on an analytical balance, and stirred at a low speed and uniform manner to ensure that the components were fully mixed to form a uniform composite material mixture. Next, a glass sheet coated with a mixture of polyacrylic acid solution and isopropanol (the mass of the polyacrylic acid solution was 5% of the mass of isopropanol) as a sacrificial layer was fixed on the rotating platform of a spin coater, and the mixture was evenly applied to the center of the glass sheet, and the mixture was spin-coated at a speed of 500rpm for 60 seconds to evenly cover the surface of the glass sheet to form a thin film.
[0047] After spin coating, the glass sheet is transferred to a hot plate at 80°C for 2 hours of heating and curing. During this process, the PDMS and phenolic resin mixture will gradually cross-link and cure to form a flexible and stretchable film structure. After curing, the glass sheet is soaked in water for 10 minutes. At this time, the sacrificial layer between the film and the glass sheet dissolves, allowing the film to be easily peeled off from the glass sheet. Use non-woven fabric to gently absorb the moisture on the surface of the film, and then place the film in a low-temperature oven at 40°C for 30 minutes to ensure that the moisture is completely evaporated, and finally a flexible film that can be directly laser engraved is obtained.
[0048] The dried film was directly laser engraved. The laser power was set to 10.5 watts and the engraving speed was set to 1440 mm / s. A 10 mm × 5 mm honeycomb rectangular pattern was engraved.
[0049] Example 2
[0050] Compared with Example 1, the difference is that 0.25 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0051] Example 3
[0052] Compared with Example 1, the difference is that 0.75 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0053] Example 4
[0054] Compared with Example 1, the difference is that when the composite material mixture is spin-coated, a glass sheet coated with a mixture of polyacrylic acid solution and isopropyl alcohol as a sacrificial layer is fixed on a rotating platform of a spin coater, the mixture is evenly coated on the center of the glass sheet, and the spin coating is performed at a speed of 200 rpm for 60 seconds. The curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0055] Example 5
[0056] Compared with Example 1, the difference is that when the composite material mixture is spin-coated, a glass sheet coated with a mixture of polyacrylic acid solution and isopropyl alcohol as a sacrificial layer is fixed on a rotating platform of a spin coater, the mixture is evenly coated on the center of the glass sheet, and the spin coating is performed at a speed of 1000 rpm for 60 seconds. The curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0057] Example 6
[0058] Compared with Example 1, the difference is that the dried film is directly laser engraved, the laser power is set to 9.5 watts, and the engraving speed is 1440 mm / s. The mass ratio of PDMS and phenolic resin, spin coating operation, curing conditions, stripping process, and laser speed are the same as in Example 1.
[0059] Example 7
[0060] Compared with Example 1, the difference is that the dried film is directly laser engraved, the laser power is set to 11.5 watts, and the engraving speed is 1440 mm / s. The mass ratio of PDMS and phenolic resin, spin coating operation, curing conditions, stripping process, laser speed are the same as in Example 1.
[0061] Example 8
[0062] Compared with Example 1, the difference is that the dried film is directly laser engraved, the laser power is set to 10.5 watts, and the engraving speed is 1080 mm / s. The mass ratio of PDMS and phenolic resin, spin coating operation, curing conditions, stripping process, and laser power are the same as those in Example 1.
[0063] Example 9
[0064] Compared with Example 1, the difference is that the dried film is directly laser engraved, the laser power is set to 10.5 watts, and the engraving speed is 1800 mm / s. The mass ratio of PDMS and phenolic resin, spin coating operation, curing conditions, stripping process, and laser power are the same as those in Example 1.
[0065] The following comparative examples are provided to demonstrate that not all flexible materials and phenolic resin combinations can produce films that can be directly laser engraved.
[0066] Comparative Example 1
[0067] Using an analytical balance, 0.5 g of each of Part A and Part B of EcoFlex silica gel and 0.5 g of phenolic resin powder were taken at a mass ratio of 1:1, and stirred at a low speed and uniform manner to ensure that the components were fully mixed to form a uniform composite material mixture. The spin coating operation, curing conditions, stripping process, laser power and speed were the same as in Example 1.
[0068] Comparative Example 2
[0069] Compared with Comparative Example 1, the difference is that 0.25 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0070] Comparative Example 3
[0071] Compared with Comparative Example 1, the difference is that 0.75 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0072] Comparative Example 4
[0073] 1 g of waterborne polyurethane and 0.5 g of phenolic resin powder were weighed on an analytical balance and stirred at a low speed and uniformly to ensure that the components were fully mixed to form a uniform composite material mixture. The spin coating operation, curing conditions, stripping process, laser power and speed were the same as in Example 1.
[0074] Comparative Example 5
[0075] Compared with Comparative Example 4, the difference is that 0.25 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0076] Comparative Example 6
[0077] Compared with Comparative Example 4, the difference is that 0.75 g of phenolic resin powder is weighed. The spin coating operation, curing conditions, stripping process, laser power and speed are the same as those in Example 1.
[0078] Performance Testing and Characterization:
[0079] The mechanical properties of the composite materials obtained in Examples 1-3 and Comparative Examples 1-6 (the composite materials obtained in Comparative Examples 1-6 could not be completely cured) were tested. Figure 1-4 shown.
[0080] The properties of the composite materials obtained in Examples 1 and 6-9 after laser engraving were also tested, and the results are as follows: Figure 5-12 shown.
[0081] Fig.13 and 14 The SEM image of the composite material obtained in Example 1 after laser engraving and the SEM image after stretching to a strain of 40% are shown.
[0082] It should be noted that the preferred embodiments of the present invention are given in the specification of the present invention, but the present invention can be implemented in many different forms and is not limited to the embodiments described in this specification. These embodiments are not intended to be additional limitations on the content of the present invention. The purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive. In addition, the above-mentioned technical features continue to be combined with each other to form various embodiments not listed above, which are all considered to be within the scope of the present invention specification; further, for ordinary technicians in this field, they can be improved or transformed according to the above description, and all these improvements and transformations should belong to the protection scope of the claims attached to the present invention.
Claims
1. A flexible composite material that can be directly laser engraved, characterized in that: The composite material is obtained by mixing phenolic resin, PDMS and PDMS curing agent and then forming a film.
2. The flexible composite material capable of being directly laser engraved according to claim 1, characterized in that: The mass ratio of the phenolic resin to PDMS is 0.25-0.75:
1.
3. The flexible composite material capable of being directly laser engraved according to claim 1, characterized in that: The mass ratio of the PDMS curing agent to PDMS is 1:8-12.
4. The flexible composite material capable of being directly laser engraved according to claim 3, characterized in that: The PDMS curing agent includes at least one of methyltriethoxysilane, methyltripropoxysilane or γ-aminopropyltriethoxysilane.
5. A method for preparing a flexible composite material that can be directly laser engraved according to any one of claims 1 to 4, characterized in that: The method comprises the steps of uniformly mixing phenolic resin, PDMS and PDMS curing agent and coating the mixture on the surface of a substrate, and curing the mixture into a film to obtain the flexible composite material that can be directly laser engraved.
6. The method according to claim 5, characterized in that The coating is carried out by spin coating; Furthermore, the spin coating conditions are: a rotation speed of 500 rpm and a time of 60 seconds.
7. The method according to claim 5, characterized in that A sacrificial layer is coated on the surface of the substrate to facilitate separation of the flexible composite material that can be directly laser engraved from the substrate after film formation; Further, the sacrificial layer is a mixed solution of polyacrylic acid solution and isopropyl alcohol; Furthermore, the mass of the polyacrylic acid solution in the mixed solution is 5% of the mass of the isopropanol; Furthermore, the concentration of the polyacrylic acid solution is 30-40 wt.%.
8. The method according to claim 5, characterized in that The curing includes heat curing.
9. Use of the directly laser-engravable flexible composite material according to any one of claims 1 to 4 for laser engraving.
10. Use of the flexible composite material capable of being directly laser engraved according to any one of claims 1 to 4 for preparing a flexible sensor.
